Smolder behavior and emissions byproducts of aircraft composite coupons. (July 2021) - Hatch, John; Wardall, Austin; Jackson, Jerimiah; McNeilly, Ryan; Kirsh, Jacob; Parker, Ariel; Morgan, Alexander; Duran, Christin
Abstract: Carbon fiber composites are a staple in aircraft manufacturing due to their enhanced physical properties and reduced mass compared to metal alloys. In the event of a mishap where these composites are subject to high heat, such as in a fire, resin char and carbon fibers in composites have been shown to oxidize and smolder. The smolder properties and emissions byproducts of aircraft composites are not well understood. In the present study, carbon fiber composites with two polymeric resin systems, epoxy and bismaleimide (BMI), were burned via cone calorimeter at three heat fluxes (35, 50, 85 kW/m 2 ) and allowed to smolder for 30 min after the flame self-extinguished. The cone calorimeter measured parameters describing fire properties during combustion, while polycyclic aromatic hydrocarbon (PAH) and combustion gas concentrations within composite emissions were measured by commercially available instruments and cone calorimetry. Heat release rate, combustion gases, and mass loss rates all increased with heat flux for both composite resin systems. BMI composites emitted more PAHs than epoxy composites. These results suggest that higher heat flux correlates with increased composite decomposition and emissions during flaming combustion and smoldering, and that BMI composites pose a higher risk to produce PAHs and carbon monoxide during smolder than epoxy composites. Highlights: Carbon fiber composite emissions during smolder increase with incident heat flux. Bismaleimide resin system composites generate higher levels of CO than epoxy resin. Polycyclic aromatic hydrocarbons more present in bismaleimide smolder emissions. Mass loss rates during smolder increase with incident heat flux, show decomposition.